Crossing the Public/Private border: the exercise of communal power in the low mixe in Oaxaca, Mexico - Salazar Zarco, Ana Lilia (2020)
This article argues that it is possible to ‘de-patriarchalize’ power and to question the preeminence of masculine over feminine authority, which is visible both in the public and private realms. The social arrangement among the Mixe in Oaxaca Mexico proposes a shift in the exercise of power. To arrive at this idea an ethnographic study (stories and in-depth interviews) was carried out. The analysis critiques the notion of authority (in its etymological sense, originator/ promoter), adding value to the idea of service as donation to the other person. It proposes the possibility of exercising power without domination or verticality and suggests a rupture between the configuration of capitalist-patriarchal the state-runned forms of public power and the private power managed by capital. Likewise, the notions of political power and their influence, are revised from the experience of the Mixe indigenous communal power.